Gen Z’s Eco-Beauty Buying Behavior: Exploring the Mediating Role of Word-Of-Mouth Communication - Maulina, Evaf; Fajariana, Dewi Endah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
Integrating Value-Belief-Norm (VBN) and Self-Perception Theory, this research examines the behavioral dynamics of Indonesian Generation Z consumers toward eco-friendly beauty products. Employing a predictive-exploratory approach with PLS-SEM analysis on 221 respondents, the findings reveal that product quality and brand image do not directly dominate purchase decisions. Instead, their influence is strongly mediated by Word-of-Mouth (WOM). The results indicate a significant paradigm shift: for Gen Z, WOM is not merely an information channel but a vital tool for identity validation. By sharing experiences, consumers engage in self-observation that reinforces their self-concept as ethical individuals. Methodologically, rigorous HTMT and VIF testing ensure the robustness of these findings. In conclusion, eco-beauty products now function as instruments of social signaling, where tangible product effectiveness triggers purchase commitment more effectively than abstract environmental claims. WOM acts as the primary catalyst, crystallizing loyalty through the reinforcement of the consumer's green identity within the digital ecosystem.